2018
DOI: 10.1111/tme.12505
|View full text |Cite
|
Sign up to set email alerts
|

Best practice in critical care: anaemia in acute and critical illness

Abstract: Anaemia is common in critical illness, and standard treatment is red blood cell (RBC) transfusion, typically using a restrictive transfusion threshold of 70 g L . However, there are subgroups of patients in whom it is biologically plausible that a higher transfusion threshold may be beneficial, namely, acute sepsis, traumatic brain injury and coexisting cardiovascular disease. In this review article, we will discuss the pathophysiology of anaemia, as well as its prevalence and time course. We will explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 103 publications
0
28
0
4
Order By: Relevance
“…RCTs in paediatric as well as in adult critically ill patients have demonstrated that restrictive red blood cell (RBC) transfusion strategies are equal or non-inferior to liberal strategies with regard to organ function and outcomes [50]. Although certain subpopulations might benefit from a higher haemoglobin levels, an RBC transfusion target of 7 g/dL is recommended in hemodynamically stable patients [51]. Whether the same target can be extended to brain-dead donors is unclear [8] since no RCTs have addressed this issue, or have examined the effect of transfusion on oxygen delivery (DO 2 ) to tissues or organs.…”
Section: Anaemiamentioning
confidence: 99%
“…RCTs in paediatric as well as in adult critically ill patients have demonstrated that restrictive red blood cell (RBC) transfusion strategies are equal or non-inferior to liberal strategies with regard to organ function and outcomes [50]. Although certain subpopulations might benefit from a higher haemoglobin levels, an RBC transfusion target of 7 g/dL is recommended in hemodynamically stable patients [51]. Whether the same target can be extended to brain-dead donors is unclear [8] since no RCTs have addressed this issue, or have examined the effect of transfusion on oxygen delivery (DO 2 ) to tissues or organs.…”
Section: Anaemiamentioning
confidence: 99%
“…Moreover, iron has multiple regulatory effects on immune function, among others blocking anti-microbial immune pathways or stimulating the production of the anti-inflammatory cytokine IL-10 [ 10 ]. As a consequence, this functional iron deficiency leads to anemia of inflammation (AI) or anemia of chronic disease (ACD) which is also found in critically ill patients [ 11 , 12 ] (Additional file 1 ). ACD is diagnosed upon the presence of reduced hemoglobin levels, increased concentrations of inflammation markers, low circulating iron levels, a reduced saturation of transferrin, along with normal or increased concentrations of ferritin [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with sepsis or septic shock are often anemic and undergo red blood cell (RBC) transfusion. This intervention may restore the balance between oxygen supply and demand by increasing oxygen delivery into tissue [1, 2]. However, RBC transfusion may also lead to deleterious events such as cardiovascular overload, acute kidney injury, acute lung injury, infectious complications, and immunomodulation [3–5].…”
Section: Introductionmentioning
confidence: 99%